COCONUT LEAF WASTE PROCESSING WITH BIODRYING PROCESS AS RAW MATERIAL FOR BIOMASS PELLETS IN WASTE TO ENERGY - Ulhasanah, Nova; Sarwono, Ariyanti; Yosafaat, Michael; Filippi, Dennis; Sari, Mega Mutiara; Suryawan, I Wayan Koko (ASTONJADRO, 2021)
Coconut leaf waste is a type of waste that contains a good enough calorific value to be used as raw material for biomass pellets. The minimum standard calorific value of biomass in Indonesia according to SNI 8675:2018 is 16.05 MJ/kg. Meanwhile, based on the research results, the calorific value of coconut leaf waste has a value of 13.34 MJ/kg. The way that can be applied to increase the calorific value is by biodrying. This study aimed to determine the effectiveness of the biodrying process in processing coconut leaf waste. This study use bioactivators in the form of tempe yeast, baker's yeast, and tapai yeast. Mass loss and moisture reduction can be achieved, respectively, 8.25-17.62% and 62.4-65.6%. The calorific value can reach the minimum standard after seven days of processing with a value of 17,995-18,623 MJ/kg.